Use of immunocytochemistry and biotinylated in situ hybridisation for detecting measles virus in central nervous system tissue. Issue 4 (April 1990) - McQuaid, S; Isserte, S; Allan, G M; Taylor, M J; Allen, I V; Cosby, S L
Abstract : Optimised immunocytochemical (ICC) and in situ hybridisation (ISH) protocols for long term, formalin fixed, central nervous system tissue infected with measles virus were developed. The effectiveness of 10 proteases for the enzymatic unmasking of formalin fixed antigen and nucleic acid was investigated. Protease VIII gave maximal signal generation with optimal tissue preservation and no background staining for both techniques. The use of a microwave oven as an additional pre-hybridisation step for RNA-RNA in situ hybridisation produced a significant increase in the number of cells labelled for genomic RNA. The ability to show the presence of antigen and nucleic acid in long term, formalin fixed tissue facilitates the use of stored necropsy material available in pathology departments for ICC and ISH investigations.